Formulation of Glipizide Tablets using Fenugreek Seed Mucilage: Optimization by Factorial Design (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: Fenugreek seed has antidiabetic activity. It also contains a major proportion of mucilage. This research work aims to develop glipizide tablets using fenugreek seed mucilage (FSM). Materials and Methods: The mucilage was extracted by double distilled water and precipitated with ethanol. The tablet utilizing the mucilage was prepared by wet granulation method. Full 32 factorial design was applied to study the effect of amount of FSM (X1) and amount of microcrystalline cellulose (X2) on release of drug at 1 h, Q1 (Y1), at the end of 12 h, Q12 (Y2), and time taken to release 50% of drug, t50% (Y3). Diabetes was induced in Wistar albino rats using streptozotocin, and effect of formulation on blood glucose level was determined. Results and Discussions: All evaluated parameters for tablet were found within the limits of the United States Pharmacopeia NF 24/19. Fourier transform infrared spectrum reveals that there is no incompatibility between the ingredients. It was observed that the selected independent factors significantly affect the dependent responses. Independent factors, X1 and X2, have a negative and positive effect on the dependent responses, respectively. Formulation brought blood glucose level to normal at the end of the antidiabetic study, however, group treated with glipizide alone was still showing elevated blood glucose level. Conclusion: It can be concluded that FSM can be used to formulate glipizide tablets and formulation shows better hypoglycemic activity than glipizide alone. This may be attributed to the antidiabetic activity of fenugreek seeds itself.